Perceptions of the Value of a Management Information System - Gallagher, Charles A. (Academy of Management Journal, 1974)
A method for determining the monetary value of an existing MIS report is presented based on user perceptions and the semantic differential technique. An empirical test demonstrated the feasibility of the methodology and showed that information value was: (a) enhanced by participation in report design, (b) related to organizational position.